Pengaruh Workforce Agility, Job Satisfaction, dan Work Engagement terhadap Adaptive Perfomance Karyawan PT. MMT Buana Logistik - Muhammad Farhan; Hendri Herman; Mefri Yudi Wisra (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of workforce agility, job satisfaction, and job engagement on employee adaptive performance at PT. MMT Buana Logistik. The dynamic logistics industry requires employees who have high adaptability to technological changes and operational demands. This type of research is quantitative causality with an explanatory approach. The population in this study were all employees of PT. MMT Buana Logistik, totaling 49 people, with the sampling technique used saturated sampling (census). Data were collected through questionnaires with a 5-point Likert scale. Data analysis techniques used included instrument testing (validity and reliability), testing of classical assumptions (normality, multicollinearity, and heteroscedasticity), and multiple linear regression analysis. Hypothesis testing was carried out through t-tests (partial), F-tests (simultaneous) and coefficient of determination (R2). The results showed that workforce agility, job satisfaction, and job engagement partially and simultaneously have a positive and significant influence on employee adaptive performance. These findings imply the importance of managing work flexibility, fulfilling employee satisfaction, and increasing work engagement to build adaptive human resources to support company competitiveness in the logistics industry.